Projected climate change over Southeast Asia simulated using a WRF regional climate model - Chotamonsak C. (2014)
Dynamical downscaling of a global climate model is applied at 60-km horizontal resolution to project changes from 1990-1999 to 2045-2054 of temperature and precipitation over Southeast Asia. The regional climate model reproduces the observed spatial distribution of temperature well, with a cold bias for maximum temperatures and a warm bias for minimum temperatures. Wet-season precipitation is simulated with less skill than dry-season precipitation. Projected warming varies from < 0.1 to 3 °C depending on the location and season, with greater warming at night than daytime for all seasons. Precipitation increases on average, with local decreases in the dry season. © 2011 Royal Meteorological Society.